Development of a new OpenFOAM solver for plasma cutting modeling. (15th June 2022) - Godinaud, Nicolas; Boivin, Pierre; Freton, Pierre; Gonzalez, Jean-Jacques; Camy-Peyret, Frédéric
Abstract: A new OpenFOAM solver is presented, for the simulation of plasma cutting torches. The mathematical model that is introduced is based on the compressible Navier–Stokes equations coupled via source terms to the electric current conservation equation. Due to the conservative and hyperbolic nature of the model, a Godunov-type scheme is used for the first time in the context of plasma cutting simulation. The numerical method consists of a second-order Total Variation Diminishing (TVD) integration with flux Harten–Lax–van Leer-Contact (HLLC) Riemann solver for the flow conservation equations, coupled with a Laplace solver for the current conservation equation. An efficient formulation for the equation of state, accurately taking into account the plasma properties, is also presented. The solver is validated through a set of canonical test cases (shock tubes and 2D Riemann problems) and it is used to simulate a three-dimensional plasma cutting torch. Good agreement is found with the literature, with an improvement in the ability to deal with the shocks occurring during plasma cutting. Highlights: A conservative and hyperbolic model for plasma cutting simulation is introduced. Godunov-type numerical scheme with HLLC Riemann solver coupled with Laplace solver. Efficient interpolations of thermodynamic properties of plasma. Better robustness and accuracy for capturing the shock waves in the plasma jet.